North Atlantic Treaty Organization (a study in the establishment and expansion) (Journal of the College of Basic Education, 2023)
Brzezinski wrote in his book (Global Chaos), as he looks ahead to the future of the world, thatThe importance of the military force will not decline to lower levels, despite the rising importance of the force.Economic, this means that humanity is on the way to consolidating defensive foundations in a world that is declining one day.one after another towards disputes of different levels and the decisive tool in all of this is the toolmilitary.The phenomenon of military alliances came in response to the desire of political leaders to achieve a kind ofSecurity is either lost, which they seek to recover, or it is present, which they try to consolidate. Few of them areThe aim behind this is to seize and control others, and NATO does not come out.Rather, he proves this rule, especially in the first stage of its inception.With the development of international relations over a successive period of time, the development of the allianceAlso in terms of goals and functions, until it became closer to a bloc to achieve huge goals.It is commensurate with the enormity that has affected the meaning of security in the Western concept, and it expands according toA new vision that adopts a pre-emptive war as an effective strategy to achieve security.Naturally, this transformation that took place in NATO in terms of development and expansionThe position of the other side (Russia), which has always represented one side of the security equationin the world, and it is logical that this position should be compatible with the international and domestic circumstances of thisA country that is experiencing states of economic weakness in its transitional period.In order to clarify all of this, this study (NATO study inOrigin and Expansion) with a hierarchical structure and two chapters. The first dealt with the establishment of the alliance and the development ofand its functions through two chapters, the first of which dealt with the establishment and development of the alliance, and the secondfunctions entrusted to him in a while. In the second chapter, we discussed the expansion of the alliance and the positionThe Russian side from this expansion also through two topics, the first of which included the expansion of the alliance, whileThe second shows the Russian position on this expansion.